Acoustic in-ice positioning in the Enceladus Explorer project. Issue 68 (2014) - Eliseev, Dmitry; Heinen, Dirk; Helbing, Klaus; Hoffmann, Ruth; Naumann, Uwe; Scholz, Franziska; Wiebusch, Christopher; Zierke, Simon
Abstract: The Enceladus Explorer project is a preparatory study for a future space mission to Saturn's moon, Enceladus. Its ultimate goal is to probe liquid-water pockets below the ice surface of Enceladus for signatures of life. A probe could be based on the IceMole concept, which melts curved trajectories through the ice. In the Enceladus Explorer project, a specialized IceMole probe for a terrestrial test scenario is in development. The goal of this exploratory study is to probe water from a liquid crevasse close to Blood Falls at Taylor Glacier, Antarctica. To navigate such a probe it is essential to be able to determine its position and monitor its trajectory. Part of the navigation system is the in-ice acoustic positioning system. For this, the head of the IceMole is equipped with acoustic sensors, which receive signals from synchronized acoustic emitters situated at the ice surface. Based on the measured propagation times, the speed of sound in ice and the positions of the emitters at the surface, the position of the IceMole can be determined by trilateration techniques. Here we present the developed acoustic positioning system, which is designed to track the in-ice melting probe up to distances of 100 m in glacier ice. Results from full-system tests in water and a first field test on Morteratschgletscher, Switzerland, are discussed.